Embryonic mortality of Indian major carps in some eco-hatchery systems - Rath, S C; Mondal, B; Gupta, S D (Indian Journal of Fisheries, 2011)
Indian major carps viz. Catla catla (Ham.), Labeo rohita (Ham.), and Cirrhinusmrigala (Ham.) are induced bred in eco-hatchery system. Mortality of developingembryo in the incubation system are common which have been investigatedat different eco-carp hatcheries in India during 1986-2000. Investigation andexperiments were conducted by repeating breeding and incubating the eggs simulatingthe conditions under which mortality occurred earlier. The investigationshave revealed that mortality incidences are due to various factors such asshedding of unprime gametes, teratogenic developments and prematurehatchings which are usually followed by fungal infestations. Ovulated oocytes,if not activated, do not imbibe water and die instantly. Some eggs are activatedbut do not cleave and pass away. Some activated eggs undergo teratogenic developmentat different stages of embryogenesis such as unequal cleavage, erosionof active blastomeres and improper gastrulation. The teratogenic embryoeither died before hatching or hatched out as deformed hatchling but later dieddue to innate deficiencies. Embryonic mortality instances are recorded moreduring early and delayed spawning. Partial or mass mortality is also caused bychoriolysis and premature hatching. Choriolysis occur due to low oxygen tension(3 ppm) and higher total alkalinity (> 150 ppm) followed by fungal infestation.When embryonic mortality was considerably high (30%-40% of total eggs),usually it led to mass mortality. Some precautionary measures and simple hatcherymanagement practices have resolved the problem.